Critical role of endoplasmic reticulum stress in chronic endothelial activation−induced visual deficits in tie2‐tumor necrosis factor mice. Issue 10 (27th July 2018) - Lenin, Raji; Nagy, Peter G.; Alli, Shanta; Rao, Vidhya R.; Clauss, Matthias A.; Kompella, Uday B.; Gangaraju, Rajashekhar
Abstract: Diabetic retinopathy (DR) is the leading cause of vision loss among working‐age adults. The interplay between hyperglycemia and endothelial activation in inducing endoplasmic reticulum (ER) stress pathways and visual deficits in DR is not fully understood. To address this, we used a mouse model of chronic vascular activation using endothelial‐specific tumor necrosis factor‐α (TNF‐α)‐expressing (tie2‐TNF) mice to induce diabetes with streptozotocin. At 4 weeks post streptozotocin, a significant 2‐fold to 10‐fold increase in retinal neurovascular inflammatory gene transcript response in tie2‐TNF mice was further increased in diabetic tie2‐TNF mice. A decrease in visual acuity and scotopic b‐wave amplitude in tie2‐TNF mice was further accentuated in diabetic tie2‐TNF mice and these changes correlated with a multi‐fold increase in retinal ER stress markers and a reduction in adherens junctions. Cultured retinal endothelial cells showed a significant decrease in trans‐endothelial resistance as well as VE‐cadherin expression under TNF‐α and high glucose stress. These changes were partly rescued by tauroursodeoxycholic acid, a potent ER stress inhibitor. Taken together, constant endothelial activation induced by TNF‐α further exacerbated by hyperglycemia results in activation of ER stress and chronic proinflammation in a feed forward loop ultimately resulting in endothelial junction protein alterations leading to visual deficits in the retina. Inhibition of ER stress and endothelial activation may prove to be a novel therapeutic target in DR. Abstract : Using a constant endothelial activation animal model of diabetes, we show that chronic inflammatory activation of vascular endothelial cells and hyperglycemia promotes visual defects downstream of ER stress signaling. Whether endothelial activation with increased TNF‐α levels observed in our diabetic model is part of a feed forward loop of ER stress leading to chronic retinal inflammation is worth pursuing further, with specific inhibitors to design therapies that address both ER stress and endothelial activation.